2008
DOI: 10.1128/jcm.00168-08
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Parechovirus in The Netherlands in 2000 to 2007

Abstract: Infection with human parechovirus 3 (HPeV3) was described for the first time in Japan in 2004 and reportedly is more often associated with severe disease than infection with HPeV1 or HPeV2. In 2004, infections with HPeV3 were observed for the first time in The Netherlands. Genetic analysis showed several different lineages, suggesting endemic circulation. We analyzed 163 cell culture isolates from the same number of patients tested in routine virological laboratories as part of the national enterovirus surveil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
124
4
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 18 publications
(20 reference statements)
13
124
4
5
Order By: Relevance
“…HPeV3 infections were predominantly associated with neonatal sepsis and CNS infections while children infected with HPeV1 had milder symptoms (Benschop et al, 2006a). These findings were later confirmed by others, increasingly detecting this type in the CSF of children with CNS disease, such as meningitis and encephalitis, as well as neonatal sepsis (Harvala et al, 2009;Levorson et al, 2009;van der Sanden et al, 2008;Verboon-Maciolek et al, 2008a;Wolthers et al, 2008).…”
Section: Hpev Infections From Mild To Severe Diseasesupporting
confidence: 61%
See 2 more Smart Citations
“…HPeV3 infections were predominantly associated with neonatal sepsis and CNS infections while children infected with HPeV1 had milder symptoms (Benschop et al, 2006a). These findings were later confirmed by others, increasingly detecting this type in the CSF of children with CNS disease, such as meningitis and encephalitis, as well as neonatal sepsis (Harvala et al, 2009;Levorson et al, 2009;van der Sanden et al, 2008;Verboon-Maciolek et al, 2008a;Wolthers et al, 2008).…”
Section: Hpev Infections From Mild To Severe Diseasesupporting
confidence: 61%
“…HPeV4 is frequently found in stools as well (Benschop et al, 2008c(Benschop et al, , 2010aBoros et al, 2010;Pham et al, 2011b;Zhong et al, 2011), while HPeV6 seems to prevail as a secondary respiratory pathogen (Harvala et al, 2008). Infections with HPeV2 and 5 are reported sporadically (Benschop et al, 2010a;Ehrnst & Eriksson, 1996;van der Sanden et al, 2008). Circulation patterns of the newly reported HPeV types 7-16 are yet to be determined (Benschop et al, 2008c(Benschop et al, , 2010avan der Sanden et al, 2008).…”
Section: Epidemiology Of Hpev In Relation To Cns Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like HPeV3, HPeV8 lacks the RGD motif; some researchers have suggested that HPeV3 may use a different receptor than other HPeV types for cell entry (3,13). Of all HPeV types, type 3 has been most strongly asso- ciated with severe neurologic and systemic clinical conditions (10,11,15). The lack of an RGD motif might implicate a different cell or tissue tropism for HPeV8 as well.…”
Section: Resultsmentioning
confidence: 99%
“…HPeV-3 was first isolated in 1999 from an infant with severe CNS disease [94], and since then different studies have recognized it as the most or second most prevalent virus causing CNS infections in infants under three months old [7,[95][96][97][98]. Outbreaks of HPeV-3 usually occur in the summer/autumn seasons and have a distinct biennial pattern [96,98].…”
Section: Human Parechovirusmentioning
confidence: 99%